Analyzing non-muslim characteristics buying halal products in Petaling Jaya, Selangor - Rajandran, Thurga; Saleh, Hasan (International Foundation for Research and Development, 2025)
This study investigates the factors influencing non-Muslim consumers' intention to purchase halal products in Malaysia, focusing on halal awareness, halal certification, halal knowledge, and halal marketing. Using a quantitative approach, data were collected via surveys from 300 respondents at malls in Petaling Jaya and analyzed using SPSS version 29. The results reveal that halal certification and marketing strategies have a significant positive impact on purchase intention, while awareness and knowledge show moderate influences. These findings highlight the critical role of certification and targeted marketing in fostering non-Muslim consumer confidence in halal products. The study contributes to the growing body of knowledge on halal consumer behavior and offers practical insights for marketers and policymakers aiming to expand the halal market beyond the Muslim community.